The Implementation of the Trial Strategy in Driving Purchase Intention on Youtube Premium - Ramadhan, Yusuf Afif; Belgiawan, Prawira Fajarindra (Journal of Consumer Studies and Applied Marketing, 2023)
The entertainment business has lately seen a transformation due to the expansion of digital platforms and the increased popularity of online entertainment. The digital age has completely transformed the entertainment industry. Businesses must adapt and embrace these changes if they want to thrive. Businesses can use the trial strategy to attract new customers despite fierce competition. Users initially assume they do not need it and are prepared to pay for supplemental services for things they typically use for free. Users become uneasy when they stop receiving their benefits and realize they require these extra services. This motivates people to purchase further services voluntarily. The execution of the trial strategy and perceived quality, price, satisfaction, and value are discussed in connection to how they affect customer purchase intention. Trial strategy and perceived price are independent variables. Perceived value, satisfaction, and quality then function as mediating variables. Also, purchase intention is the dependent variable. An online survey with 336 participants was undertaken. The findings from quantitative methodologies demonstrate that trial strategy, perceived value, and satisfaction have a direct, positive, and significant impact on purchase intention. In the meanwhile, buying intention is indirectly impacted by perceived quality and price.